Identification of Ectoparasite Infection in Tilapia (Oreochromis niloticus) Based on Water Quality in Rawa Pening - tholibah mujtahidah; Sri Hidayati; Ninik Ambarwati (Journal of Aquaculture Development and Environment, 2022)
Testing of ectoparasites on water quality in infections that occured in tilapia in aquaculture activities in Rawa Pening. The purpose of this study was to determine the exposure to the abundance of ectoparasite bacteria that infected the growth of tilapia in Rawa Pening. This study used experimental method and purposive sampling with data processing in a descriptive survey. The data analysis used was analysis of variance (ANOVA) with the aim of knowing the effect of sampling and the parameters tested, this test was carried out 4 (four) times for water quality and ectoparasite observations 3 (three) times for testing to obtain the accuracy of data sampling. The results of this study showed that there was an infection with levels of ectoparasites identified from the types of Streptococcus sp, Lernaea sp, Aeromonas sp, and Trichodina sp. These bacteria attack fish with the highest number or total exposure in the Tuntang area. The reason was, currently water hyacinth was being cut down as one of the local government programs to reduce the blooming of water hyacinth (Eichhornia crassipes) of 7.92 mg/L, pH levels 7.59, ammonia levels 10-20 mg/L and nitrate levels 0.5 mg/L were still in optimal conditions from the results carried out.